PENDAMPINGAN PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN MELALUI PENGENALAN MAKHARIJUL HURUF MENGGUNAKAN METODE SOROGAN - Dewi Anita; Siswanto (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
The low reading accuracy of Al-Qur’an students (santri), particularly in the mastery of Makharijul Huruf (the correct articulation points of Arabic letters), presents a key challenge for the TPQ (Qur'anic Education Park) Sapu Jagad in Pakis Village, Magelang Regency. The main objective of this community service program (PkM) is to enhance the students' Al-Qur’an reading ability through the optimization of the Sorogan Method integrated with a focused introduction and practice of Makharijul Huruf. This PkM activity utilizes the Asset-Based Community Development (ABCD) approach, leveraging the traditional Sorogan method as a local asset. Data was collected through initial observation, interviews, and Focus Group Discussions (FGD) to identify specific needs. The program implementation focused on intensive mentoring, where the Sorogan Method served as the primary platform for real-time correction of problematic letter articulation, supported by a guide book for hijaiyah makharijul huruf pronunciation. The results of this program demonstrate that the application of the Sorogan Method, specifically targeting the introduction of makharijul huruf, significantly improved the students' Al-Qur’an reading skills. Through this integrated method, students were able to read the Qur’an fluently, smoothly, and in accordance with the precise articulation points.